2021
DOI: 10.1149/1945-7111/abfd73
|View full text |Cite|
|
Sign up to set email alerts
|

Review—Reversible Heat Effects in Cells Relevant for Lithium-Ion Batteries

Abstract: We review measurements of reversible heat effects in lithium-ion batteries, i.e. entropy changes and Seebeck coefficients of cells with relevant electrodes. We show how to compute the Peltier heat of battery electrodes from Seebeck coefficients. The Seebeck coefficient depends on the heat of transfer (Soret effect), which is found from the difference of initial and stationary state values of the Seebeck coefficient. We apply non-equilibrium thermodynamics theory and obtain initial Peltier heats not reported be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…The reason for a larger shift of anodic than cathodic peaks in CVs as temperature increased (Figure ) is due to the reversible heat effects in intercalation battery electrodes which are related to the entropy changes . The temperature dependence of the OCP for each ion in the temperature range of 15 to 75 °C was used to calculate free energy components (entropy and enthalpy) (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for a larger shift of anodic than cathodic peaks in CVs as temperature increased (Figure ) is due to the reversible heat effects in intercalation battery electrodes which are related to the entropy changes . The temperature dependence of the OCP for each ion in the temperature range of 15 to 75 °C was used to calculate free energy components (entropy and enthalpy) (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…32 The reason for a larger shift of anodic than cathodic peaks in CVs as temperature increased (Figure 1) is due to the reversible heat effects in intercalation battery electrodes which are related to the entropy changes. 53 The temperature dependence of the OCP for each ion in the temperature range of 15 to 75 °C was used to calculate free energy components (entropy and enthalpy) (Figure 2a). The increase in temperature resulted in a shift of OCP of all of the four ions to a more negative position, which was consistent with a negative temperature coefficient (ΔE/ΔT) in the literature for a PBA-based electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, such an entropy-Se relation was also found to play a crucial role in the thermal modelling of batteries. 45 In 1979, Weaver and co-workers showed that DS rc between the reduced and oxidized forms of transition-metal redox couples (M II/III ) could readily be obtained using non-isothermal electrochemical cells, 46 which formed the basis of TEC. Notably, a much larger DS rc was found for Co II/III compared with those for other transition metals; this observation was explained by the greater metal-ligand bond stretching induced by the (t 2g ) 6 -(t 2g ) 5 (e g ) 2 transition upon the reduction of the Co III species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, such an entropy-Se relation was also found to play a crucial role in the thermal modelling of batteries. 45…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, measurements of the reversible heat give specific information on electrode processes. In the case of batteries, the reversible heat corresponds to T ∆S, where T is the absolute temperature and ∆S is the entropy change, which can also be obtained from the temperature-dependence of the open circuit potential [51,50,102,103,104,105]. In the case of porous capacitive electrodes, the reversible heat of (dis)charging the capacitor informs on changes in the state of the electrical double layer inside the pores.…”
Section: Introductionmentioning
confidence: 99%